Corrosion-resistant alloy testing and selection for oil and gas production. (13th March 2018) - Sridhar, Narasi; Thodla, Ramgopal; Gui, Feng; Cao, Liu; Anderko, Andre
ABSTRACT: Corrosion-resistant alloys (CRAs) are employed in severe oil and gas production environments that operate at high pressures and temperatures and contain chlorides, CO2, and H2 S. They exhibit high resistance to uniform corrosion in these environments due to their passivity. However, they can suffer from different forms of environmentally assisted cracking (EAC), depending on the environmental and metallurgical conditions. This paper reviews the recent literature of EAC in CRAs and presents an overall framework for evaluating the SCC based on electrochemical modelling of corrosion and repassivation potentials for localised corrosion. The modelling is supported by experimental data on crack growth as a function of environmental variables, alloy content, and potential. This paper is part of a supplementary issue from the 17th Asia-Pacific Corrosion Control Conference (APCCC-17) .